THEORETICAL ASPECTS OF SOCIAL CAPITAL FORMATION IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Ruda T.V., Nagorichna O.S. THEORETICAL ASPECTS OF SOCIAL CAPITAL FORMATION IN UKRAINEPurpose. The aim of the article is to research features of domestic approaches to interpretation of essence, structural filling and specifics of formation of social capital in Ukraine.Methodology of research. The following methods are used to achieve this goal: induction and deduction, theoretical generalization, abstraction, dialectical cognition – in the study of scientific sources and research of theoretical aspects of social capital formation in Ukraine, including the interpretation of the definition of “social capital” by domestic scientists and identification of social capital; graphic – to visualize the components of social capital; abstract and logical – to generalize theoretical positions, to form conclusions and proposals on the research topic.Findings. The analysis of the main approaches to the interpretation of the category “social capital” is accumulated and carried out. Common and different features between the proposed interpretations are identified. The peculiarities of social capital as an economic category are studied and its role in the development of the state is noted. The main approaches to the classification of this concept are identified. The structural content of social capital is revealed. The necessity of research of the branch level of social capital is actualized and the specifics of its development under modern conditions in Ukraine are outlined. The main directions of social capital formation in Ukraine are determined.Originality. The study of theoretical aspects of social capital formation has been further developed, in particular, approaches to defining the essence of the category of “social capital” are generalized and the main directions of its formation at the state level are outlined.Practical value. The main provisions of this study can be used in the process of developing proposals for the formation of a model of social capital development in Ukraine.Key words: social capital, branch social capital, social relations, trust, positive social capital, negative social capital, society, structure of social capital.
Keywords: Key words; social capital; branch social capital; social relations; trust; positive social capital; negative social capital; society; structure of social capital.